Quadrennial Defense Review (QDR) analysis : a retrospective look at Joint Staff participation - Schrader, John Y.; Lewis, Leslie; Brown, Roger Allen, 1940-; International Security and Defense Policy Center; National Defense Research Institute (U.S.); Rand Corporation; United States. Joint Chiefs of Staff (Santa Monica, CA : RAND, 1999)
The 1996 Quadrennial Defense Review (QDR) was intended to evaluate the state of the U.S. military and propose improvements. RAND was asked to review the Joint Staff's participation in the QDR and to make recommendations to aid future reviews. As this study shows, the QDR goal of integrating processes and organizations was not successful. For a variety of reasons, primarily the lack of external pressure for a serious review, the QDR did little to change the status quo. One of RAND's most crucial recommendations was the need for the Joint Staff to increase its involvement and improve its position as an "integrator" during the course of the review process. Many of RAND's suggestions are already being implemented. This should be further encouraged through leadership reviews of the state of the analytical "toolbox" and examinations of major issues in the QDR. It is imperative that the Joint Staff increase its role in future reviews because only when a serious program to develop capabilities and take responsibilities is implemented will military judgments be translated into effective advice.
"National Defense Research Institute."
Includes bibliographical references (p. 103-106).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Military planning -- United States; National security -- United States; Strategy; United States -- Armed Forces -- Operational readiness; United States -- Military policy